Influence of Psychological Empowerment on Organizational Citizenship Behaviour in the Public Sector in Jaffna District - Raveendran, T. (Eastern University, Sri Lanka, 2022)
There are little evidences regarding the association between psychological empowerment and organizational citizenship behavior in the Sri Lankan context. In addition, there are conflicting findings regarding the linkage between the variables. Thus, the main objective of the current study is to examine the influence of Psychological Empowerment (PE) on Organizational Citizenship Behavior (OCB). Particularly this study examines the specific dimensions of PE that are linked to the extra role behaviour among the employees. For the purpose of the study, 461 employees working in the public sector organizations in Jaffna District were selected as sample based on convenience sampling method. The established instruments were used for measuring the constructs and a cross sectional survey method was employed. The results revealed that the PE cognitions namely meaning and competence positively influence OCB whereas the influence of the cognitions namely self-determination and impact on OCB is not significant. The results of the present study suggests that organizations need to pay attention to promote the perception among the employees that they are empowered in order to enhance OCB.
Keywords: Psychological empowerment; Organizational citizenship behaviour; Public sector